The EU as a normative power? Fighting greenwashing and promoting the integrity of corporate climate action within and outside Article 6 of the Paris Agreement - Nico Kreibich; Max Schulze-Steinen (Wuppertal Institut für Klima, Umwelt, Energie, 2023)
This policy brief explores different options for the EU to promote the integrity of corporate climate action through activities within as well as outside the EU and partially making use of the Article 6 infrastructure. Taking into consideration the new framework conditions established with the adoption of the Paris Agreement, the paper outlines different options of how the EU could push towards more integrity and fight greenwashing.
urn:nbn:de:bsz:wup4-opus-83982
Keywords: 360